HPLC-DVD combined with chemometrics to analyze the correlation between the Q-marker content and color of Corni Fructus. Issue 9 (27th April 2022) - Wang, Ting; Bai, Yilin; Du, Yating; An, Shujing; Han, Binkai; Yang, Xiaolin; He, Changfen; Sun, Haoqiang; Zhao, Ke; Xue, Xiaochang; Kang, Jiefang
Abstract : A standard colorimetric card related to Corni Fructus (CF) quality was established, which simplified the quality evaluation process and improved the accuracy of the visual evaluation of CF. Abstract : Although Corni Fructus (CF) is a fruit with great economic value and development potential in medicine and food, too much reliance on personal experience for quality evaluation seriously limits the trading and circulation of CF. In the present study, through the research on the correlation between the chemical composition and the appearance color, a standard colorimetric card related to CF quality was established, which simplified the quality evaluation process and improved the accuracy of the visual evaluation of CF. Firstly, a total of 29 batches of CF from different places were collected. Then, "imread" in the MATLAB software was used to convert the color of all samples into RGB values, and HPLC-DVD was used to measure the content of the main chemical components in CF. Thereafter, the correlation between the content and color was studied by using MLR, BP-ANNs and SVM chemometric tools to screen the Q-marker of CF, which was further confirmed by in vivo and in vitro experiments. Finally, the Q-marker standard colorimetric card with the best fitting degree is established according to the prediction model. Thus, this study provides an auxiliary reference for the color evaluation of CF and a reference for the standardization and quantification of the macro characteristics of traditional Chinese medicine and food.